Order Hymenoptera. In: Zhang, Z.-Q. (Ed.) Animal Biodiversity: An Outline of Higher-level Classification and Survey of Taxonomic Richness (Addenda 2013) - Aguiar, Alexandre P.; Deans, Andrew R.; Engel, Michael S.; Forshage, Mattias; Huber, John T.; Jennings, John T.; Johnson, Norman F.; Lelej, Arkady S.; Longino, John T.; Lohrmann, Volker; Mikó, István; Ohl, Michael; et al. (Zootaxa, 2013)
An updated classification of the order Hymenoptera is provided with the current numbers of genera and species described so far specified. The order is composed of 2 suborders, 27 superfamilies, 132 families, 8423 extant genera with an additional 685 extinct genera. Considered one of the most species-rich insects orders a total of 153088 extant species have been described, in addition to 2429 extinct species.